Global, regional and national burden of neck pain in children and adolescents: GBD 2021 systematic analysis - Sun, Chao; Lin, Hao; Zhang, Zhiqiang; Yang, Xinyue; Zhou, Jiaming; Wang, Rui; Xue, Yuan (Frontiers in Neurology, 2025)
BackgroundNeck pain (NP) has emerged as a significant health concern among children and adolescents, with potential lifelong consequences. This study aimed to comprehensively assess the global, regional, and national burden of NP among this population using data from the 2021 study.MethodsPublicly available modeled data and methods from the Global Burden of Disease (GBD) study 2021 were used to systematically analyze and evaluate the global burden of NP among children and adolescents. Primary outcomes were NP related age-standardized prevalence, incidence, years lived with disability (YLDs), and average annual percentage change (AAPC).ResultsBetween 1990 and 2021, the global prevalence of NP among children and adolescents increased from 8.49 million to 10.32 million cases, though age-standardized rates remained relatively stable (AAPC 0.01%). The global incidence of NP among children and adolescents increased from 3.17 million cases in 1990 to 3.82 million in 2021, while the age-standardized incidence rate showed a minimal decrease (AAPC −0.02%). The burden of NP in terms of YLDs increased from 0.89 million in 1990 to 1.08 million in 2021, although the age-standardized YLD rate remained stable (AAPC 0%). A pronounced age gradient was observed, with rates in 2021 peaking in the 15–19 years group (1,012.03 per 100,000) compared to the 5–9 years group (97.44 per 100,000), though the youngest group showed the largest relative increases over time (AAPC 0.10%). Females consistently exhibited 33.1% higher prevalence than males. High sociodemographic index (SDI) regions demonstrated the highest prevalence rates, with Western Europe (984.25 per 100,000), High-income North America (827.69), and Central Europe (751.30) leading, though low SDI regions showed more rapid increases. At the national level, Italy, Norway, and Denmark had the highest rates, while Middle Eastern countries experienced the most rapid increases.ConclusionDespite stable global age-standardized rates, the increasing absolute burden of NP among children and adolescents remains concerning. This study provides strong evidence that there are diverse changing patterns of NP burden across different sex, age, and SDI groups within children and adolescents.